Design paradigm and syntagm of woven bamboo packaging (besek) - Andika Agung Sutrisno; Bambang Sunarto; Dharsono Dharsono (Fakultas Sastra Universitas Negeri Malang, 2022)
Design paradigm and syntagm of woven bamboo packaging (besek)Abstract: Communication becomes a powerful means of cultural diffusion and an alternative choice for the community. Recently, modern society has been observed to be highly consumeristic, where the image becomes a consideration in the decision-making to purchase. Visual design on the packaging has an effect on consumers' purchasing decisions. The traditional woven bamboo packaging (besek) has an exciting phenomenon in modern society today (urban). The qualitative approach was used with narrative construction or textual descriptions of phenomena. Formal analysis and sign interpretation were used to answer research problems. The formal analytical method was used to identify the way syntagmatic shapes produce paradigms in meaning. The alternative modern packaging that follows the recent developments does not significantly replace the presence of besek as a medium to come to the collective memory of the target audience. Besek is a small part of existing past cultural products that compete with the modern packaging paradigm. Every past cultural product that successfully maintains its existence enables the establishment of an image and becomes a bridge to collective memory in the contemporary era.Keywords: paradigm, essence, memory colective, design, packagingParadigma dan syntakmatik desain kemasan anyam bambu (besek)Abstrak: Komunikasi menjadi sarana difusi budaya, sekaligus alternatif pilihan bagi masyarakat. Fenomena pada masyarakat modern kapitalis adalah konsumerisme yang sangat tinggi, dimana citra menjadi preferensi dalam menimbang sebuah keputusan untuk membeli. Visual desain pada kemasan memiliki pengaruh kepada konsumen dalam keputusan pembelian. Kemasan produk masa lalu (besek) memiliki fenomena menarik di masyarakat modern kini (urban). Pendekatan kualitatif digunakan dalam konstruksi naratif atau deskripsi tekstual atas fenomena. Analisis formal dan pendekatan interpretasi tanda digunakan untuk menjawab permasalahan penelitian. Metode analisis formal yang digunakan guna untuk mengetahui bagaimana bentuk secara syntakmatik yang akan menghasilkan paradigma dalam makna. Medium produk budaya masa lalu (besek) yang memiliki alternatif kemasan dengan wujud yang konvensional, mengikuti perkembangan ternyata tidak secara signifikan mengantikan kehadiran sebagai medium untuk masuk kedalam memori kolektif khalayak sasaran. Besek merupakan bagian kecil dari produk budaya masa lalu yang eksistensinya masih bertahan dengan segala pradigma kemasan modern yang bersaing. Produk budaya masa lalu dalam wujud apapun yang eksistensinya bertahan, secara esensial sangat memungkinkan membentuk citra dan menjadi jembatan kedalam memori kolektif di era kontemporer.Kata kunci: paradigma, esensi, memori kolektif, desain, kemasan